The Implementation of Scaffolding Strategy in Teaching Legal Translation : توظيف استراتيجية الدعائم التعليمية في تدريس الترجمة القانونية - bounekta , Mamel (Maalim, 2026)
The scaffolding strategy is considered as one of the most important teaching practices that takes into account the gradual structuring of learning materials according to the learner’s cognitive needs. It is implemented through five main stages: presentation, modelling, guided practice, semi-independent practice, and independent performance. The current study seeks primarily to examine the extent to which this strategy can help Master 1 students of legal translation to overcome the difficulties faced when rendering English legal texts into Arabic. To this end, a set of structured activities was designed to reflect the specific linguistic, stylistic, and functional features of legal discourse, enabling students to progress gradually from understanding basic concepts to more advanced levels of analysis and translation. Findings reveal that applying scaffolding in teaching legal translation significantly improves learners’ performance on multiple levels: it enhances their ability to accurately analyse source texts, develops their legal drafting skills in the target language, and increases their autonomy in making translational decisions.